Seeing the pandemic through children's eyes: Exploring Turkish children's views on COVID-19 pandemic by focus-group discussions - BORAN, PERRAN (My University, 2023)
BackgroundThe direct and indirect effects of the COVID-19 pandemic on children and youth people are well documented. Little is known about children\"s experiences of the pandemic in their own words. We aimed to explore Turkish children\"s experiences and views about the pandemic, across private and public educational systems. MethodsSix focus group discussions were conducted online with 30 children aged between 7 to 18 years in 2021. Children were enrolled through snowball sampling technique according to developmental age groups. A thematic analysis was conducted. ResultsWe identified five themes: Compliance with public health measures about preventing the spread of COVID-19, changes in daily routines, emotional responses to the pandemic, distance education, and adaptive responses. Overall, children were well informed and receptive to the public health preventive measures with the exception of older children\"s tendency to disregard physical distancing with friends. They reported frustration with those who did not comply with measures and believed that the authorities should strictly enforce public health requirements. Emotional responses comprised fear of family members and themselves being infected, anxiety produced by the uncertainty of the virus, and the loss of social support. There was a perceived disparity between students from public and private schools regarding academic self-competence. Positive aspects of the pandemic included positive interactions with family members and the acquisition of new hobbies. Although most children acknowledged the support of their parents to deal with challenges, children of health workers were particularly isolated in terms of emotional support. ConclusionOur findings offer additional insights and validate previous research on the negative and positive effects of COVID-19 from the child\"s perspective across private and public educational systems. This study contributes to global advocacy efforts aimed at understanding the impact of the pandemic on children.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Social Sciences and Humanities; Psychology; Developmental Psychology; Health Sciences; PSİKOLOJİ, GELİŞTİRME; Temel Bilimler (SCI); PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PSYCHOLOGY, DEVELOPMENTAL; PSYCHOLOGY; Natural Sciences (SCI); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Gelişim ve Eğitim Psikolojisi; Psikoloji (çeşitli); Genel Psikoloji; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Sosyal Bilimler ve Beşeri Bilimler; Developmental and Educational Psychology; Psychology (miscellaneous); General Psychology; Pediatrics; Pediatrics, Perinatology and Child Health; Social Sciences & Humanities; adolescent; children; COVID-19; online education; school closure; social isolation